eDNA metabarcoding for diet analyses of green sea turtles (Chelonia mydas) - Díaz-Abad, Lucía (2022)
Understanding sea turtle diets can help conservation planning, but their trophic ecology is complex due to life history characteristics such as ontogenetic shifts and large foraging ranges. Studying sea turtle diet is challenging, particularly where ecological foraging observations are not possible. Here, we test a new minimally invasive method for the identifcation of diet items in sea turtles. We fngerprinted diet content using DNA from esophageal and cloacal swab samples by metabarcoding the 18S rRNA gene. This approach was tested on samples collected from green turtles (Chelonia mydas) from a juvenile foraging aggregation in the Bijagós archipelago in Guinea-Bissau. Esophagus samples (n=6) exhibited a higher dietary richness (11±5 amplicon sequence variants (ASVs) per sample; average±SD) than cloacal ones (n=5; 8±2 ASVs). Overall, the diet was dominated by red macroalgae (Rhodophyta; 48.2±16.3% of all ASVs), with the main food item in the esophagus and cloaca being a red alga belonging to the Rhodymeniophycidae subclass (35.1±27.2%), followed by diatoms (Bacillariophyceae; 7.5±7.3%), which were presumably consumed incidentally. Seagrass and some invertebrates were also present. Feeding on red algae was corroborated by feld observations and barcoding of food items available in the benthic habitat, validating the approach for identifying diet content. We conclude that identifcation of food items using metabarcoding of esophageal swabs is useful for a better understanding of the relationships between the feeding behavior of sea turtles and their environment.